Trends of Remote Sensing applications for Amazon monitoring - Peña-Villacreses, Gina; Ayala-Hidalgo, Shantall; Braga, Daniel; Guimarães, Yasmim [UNESP]; Santos, Marcos Ronielly da Silva; Pereira, Marconi de Arruda; Velastegui-Montoya, Andrés (Copernicus Publications, 2024)
The Amazon is home to a vast biodiversity and plays a crucial role in the maintenance and conservation of the planet. The progress of anthropogenic activities in the region is one of the drivers of land cover change. Studying these changes through remote sensing enables the monitoring of degradation and deforestation in the Amazon rainforest. Using bibliometric tools this study analyses the different remote sensing approaches for land use and land cover monitoring in the Amazon. The methodology includes 1) data search and collection, 2) tool selection and data processing, and 3) data and trend analysis. The results indicate that studies on forest loss and biodiversity are trending in the field. Emerging topics focus on new tools for environmental impact assessment and evaluating new computational technologies for satellite data management.
Keywords: Bibliometric; Land cover; Land use; Remote sensing; Tropical forest